Students’ Anxiety in Speaking English at the Eleventh Grade of Bina Insan Mandiri Banjarsari Lebak Vocational High School - Dedeh Kurniasih; Riandi; Rizdki Elang Gumelar (Social Impact Journal, 2024)
Language is considered to be a system of communicating with other people using sounds, symbols and words in expressing a meaning, idea or thought. Speaking is the action of convey information or expressing the idea and feelings in spoken English. This research explained about analysis the anxiety students’ speaking in English at the eleventh grade of Vocational High School Bina Insan Mandiri Lebak in the academic year of 2023/2024. In this research, the researcher use qualitative approach while the research method will use descriptive qualitative method. The researcher would carry out the steps of the research, namely the process of data collection, data reduction, data display, and drawing conclusions and verification. There were three types of student anxiety in speaking English at the Eleventh Grade of Vocational High School Bina Insan Mandiri Banjarsari Lebak, they are State Anxiety, when the students feel panic and may stress when they want to speak in English, Trait Anxiety, when the students feel nervous when they do not understand the teacher explanation, and Specific-situation Anxiety, when the students should do examination about speaking. There were three factors caused the students anxiety in speaking English at the Eleventh Grade of Vocational High School Bina Insan Mandiri Banjarsari Lebak, they are communication apprehension, where the students could not speak English because they have little experience with English and do not always practice English, test anxiety, where the students feel anxious because they have to do the test that the teacher assigns to them, and fear of negative evaluation when the student are afraid of being judged negatively by their teachers and of being mocked by their classmates if they make mistakes when speaking English.